Global land carbon sink response to temperature and precipitation varies with ENSO phase. (1st June 2017) - Fang, Yuanyuan; Michalak, Anna M; Schwalm, Christopher R; Huntzinger, Deborah N; Berry, Joseph A; Ciais, Philippe; Piao, Shilong; Poulter, Benjamin; Fisher, Joshua B; Cook, Robert B; Hayes, Daniel; Huang, Maoyi; et al.
Abstract: Climate variability associated with the El Niño-Southern Oscillation (ENSO) and its consequent impacts on land carbon sink interannual variability have been used as a basis for investigating carbon cycle responses to climate variability more broadly, and to inform the sensitivity of the tropical carbon budget to climate change. Past studies have presented opposing views about whether temperature or precipitation is the primary factor driving the response of the land carbon sink to ENSO. Here, we show that the dominant driver varies with ENSO phase. Whereas tropical temperature explains sink dynamics following El Niño conditions ( r TG, P = 0.59, p < 0.01), the post La Niña sink is driven largely by tropical precipitation ( r PG, T = −0.46, p = 0.04). This finding points to an ENSO-phase-dependent interplay between water availability and temperature in controlling the carbon uptake response to climate variations in tropical ecosystems. We further find that none of a suite of ten contemporary terrestrial biosphere models captures these ENSO-phase-dependent responses, highlighting a key uncertainty in modeling climate impacts on the future of the global land carbon sink.